Cognitive evolution : from single cells to the human mind - Boles, David B. (Writer on psychology) (New York, NY : Routledge, 2022)
"Cognitive Evolution provides an in-depth exploration of the natural history of cognition, from the beginning of life on Earth to present-day humans. Drawing together evolutionary, comparative, and neuroscience research, the book brings a unique cognitive perspective to evolutionary psychology. The second edition features the latest research and illustrations on emerging topics, making it a true update of the field. After introducing evolution, Boles adopts an information processing perspective - from inputs to outputs, with all the mental processes in between to provide a systematic overview of the evolution of cognition, including its sensory, motoric, perceptual, and cognitive components. The combination of evolutionary, comparative, and neuroscience perspectives provides an insight on topics like vision, handedness, tools and planning, spatial perception, pattern recognition, memory, language, and consciousness. Cognitive Evolution is a comprehensive, essential read for advanced undergraduate and postgraduate students of cognitive and evolutionary psychology. Researchers will find it a useful and insightful synthesis of the field, yet even the curious public will find in it much that is surprising and enlightening"--
Life begins -- Life gets complicated -- Vertebrates to early mammals -- Later mammals through primates -- Humans -- The mechanical and chemical senses -- Vision -- The origins of motion -- Bipedalism -- Praxis and handedness -- Tools and planning -- Spatial perception -- Pattern recognition -- Memory -- Language -- consciousness -- A summary in nine firsts.
Keywords: Cognition; PSYCHOLOGY / Cognitive Psychology; SCIENCE / Life Sciences / Evolution; SOCIAL SCIENCE / Anthropology / General